Direct dating of human skeletal material from Ganj Dareh, Early Neolithic of the Iranian Zagros. (April 2017) - Meiklejohn, Christopher; Merrett, Deborah C.; Reich, David; Pinhasi, Ron
Abstract: We present the first set of radiocarbon dates derived from human skeletal material from Ganj Dareh, Iran. These new dates fully overlap with those on goat bone samples published by Zeder and Hesse (2000) and confirm the finding of the latter source that occupation of the site occurred within ca 200–300 years after 9000 bp (~ 10, 100 cal. BP). In so doing we confirm the absence of a hiatus between the lower two levels (E and D), an idea derived from the initial dating of the site. We also provide the first full review of the 23 radiocarbon dates from the site published prior to the work of Zeder and Hesse (2000). Examination of the full date sequence emphasizes the complexity of the site stratigraphy and tight clustering of the dates from all levels, thereby clarifying the difficulty that the excavator had in separating levels. Highlights: Report the first direct radiocarbon dates on human skeletal material from Ganj Dareh in the Iranian Zagros. Confirm that human remains are contemporary with the goat remains for which there is evidence of human control. Direct radiocarbon dates from human remains confirm that site occupation was short, 200 to 300 years ca 10, 100 cal. BP. Confirm that there was no occupational hiatus between the oldest stratigraphic levels, D and E.